Business cycles and equilibrium - Black, Fischer, 1938- (Oxford [Oxfordshire] UK ; New York, N.Y., USA : B. Blackwell, 1987)
An updated look at what Fischer Black's ideas on business cycles and equilibrium mean today. Described a view of business fluctuations based on the idea that a well-developed economy will be continually in equilibrium.
Includes bibliographies and index.
oif 04/05/15
Loan
Keywords: Business cycles; Equilibrium (Economics); General equilibrium theory; Trade cycles